Sistem Pendukung Keputusan Penentuan Penerimaan Dana BOS Pada Siswa Sekolah SMK Sinar Harapan Beringin Menggunakan Metode ARAS - T. Razeki Aditya Syahputra; Rivalri Kristianto Hondro; Rian Syahputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The problem in the process of determining candidates for receiving school operational assistance funds for students faced by the Sinar Harapan Vocational School still has several problems such as the existence of subjectivity that tends to assess candidates for receiving school operational assistance funds that still lead to personal opinions so that the assessment process takes a long time. quite long and not right on target because it is done manually so that the decision-assessment process becomes slow and this is certainly not very good because it affects the smooth operation of the Sinar Harapan Vocational School. As for the solution to overcome the problems faced by the Sinar Harapan Vocational School, a decision support system is needed to select candidates for receiving BOS funds. When choosing a method, it is necessary to use the additive ratio assessment (ARAS) method. The system will obtain a ranking decision based on each alternative choice based on a number of predetermined criteria. The alternative with the most weights is the recommended alternative. This research produces a decision support system application program. Designed using a Website-based application that will be used with a multi-user concept, which is designed only for user convenience, through this decision support system application, it is expected to facilitate the process of determining prospective BOS Fund recipients, it is expected to get the best results from the Additive Ratio Assessment (ARAS) method. . And a trial was conducted by entering a sample of 10 BOS fund recipients to determine the recipient of BOS funds. Based on the ranking of 10 candidates who are entitled to receive 2 people with a dbwah value of 0.5, namely: alternative 10 (Abdi Sutoyo) with a value of 0.3765 and alternative 9 (Ade Juanda) with a value of 0.4058